Response of Castor (Ricinus Communis L.) Varieties on Growth and Silk Production of Eri Silk Worm (Philosamia Ricini Hutt.) - Sanchan, J N; Bajpai, S P (Annals of Arid Zone, 2016)
Four castor varieties, Viz., Rossy, S20, EB 31 and EB 16 were tested to see their response to larval growth and silk production. The Rossy variety of castor proved superior in all the respects followed by S 20 EB 31 and Ell 16. From these studies it is highly suggestible that propagation of Rossy variety of Castor wiII result in increased production of silk by Eri Silk Worm.